O livro de leitura da campanha de pé no chão também se aprende a ler/RN: um estudo dos pressupostos histórico-culturais - Spinelli, Pablo Cruz (2011)
This work is about the historical and cultural assumptions inserted in the contents of literacy of the Campanha de Pé no Chão Também se Aprende a Ler, a movement of culture and popular education, developed in the State of Rio Grande do Norte in the period between 1961 and 1964. The hypothesis is the one of the existence of a romantic-political ideology which permeated a national developmentalist conception sited in its didactic-pedagogic instrument of literacy, the Book of Lecture of De Pé no Chão Também se Aprende a Ler/RN (1963). It has the aim to understand how the popular critical consciousness marked by conceptions of culture and popular education in its social, cultural and ideological relations, happened. Analyses the object of study by the symbolical cartography, methodological procedures which have as principles to retire from an antecedent source implicit meanings that can discover new realities, articulating the keywords of that document to the ideology that surrounded the Campanha de Pé no Chão Também se Aprende a Ler /RN. As results, the research showed that, considering the historical-cultural assumptions of the national developmentalist thought sited in the studied Book of Lecture, the conditions of the political-cultural context and of the advance of the Brazilian national industry on the beginning of the 1960th , admitted a process of social integration lavished by the popular literacy on the Campanha de Pé no Chão/RN, linked with the possibility of transition of the popular conscience, in a romantic-political perspective of the culture and the popular education